Lipophilic and Hydrophilic Antioxidant Capacities of Vegetables, Herbs and Spices in Eighteen Traditional Thai Dishes - Tangkanakul, Plernchai; Trakoontivakorn , Gassinee (Agriculture and Natural Resources, 2014)
A selection of 18 local dishes commonly consumed in four regions of Thailand and 42 types of vegetables as their ingredients were analyzed for their total antioxidant capacity (TAC) and total phenolic content (TPC). The TAC was calculated by combining the hydrophilic oxygen radical absorbance capacity (H-ORAC) and the lipophilic oxygen radical absorbance capacity (L-ORAC). The H-ORAC values of all vegetables ranged from 2.87 to 607.17 µmol Trolox equivalents (TE) per gram, whereas the L-ORAC values ranged from 0.17 to 262.02 µmol TE.g-1. The TAC values paralleled the H-ORAC values in most vegetables because H-ORAC makes up more than 90% of TAC. All of the vegetables analyzed contained total phenolic contents ranging from 0.29 to 10.03 mg gallic acid equivalent per gram of fresh weight (GAE.g-1). The H-ORAC, L-ORAC and TPC of all dishes showed wide ranges, from 9.82 to 44.37 µmol TE.g-1, from 0.41 to 4.85 µmol TE.g-1 and from 0.56 to 2.22 mg GAE.g-1, respectively. To make an overall evaluation, the TAC and TPC consumed per serving size must be considered. The TAC and TPC of all dishes per serving ranged from 901 to 7,237 µmol TE and from 49 to 326 mg GAE, respectively. Fifty percent of the studied dishes were found to contain a TAC level greater than 3,000 µmol TE per serving. This means that a single food item of these dishes could achieve the recommended daily allowance of antioxidants currently recommended by the United States Department of Agriculture at 3,000 to 5,000 µmol TE.